Canadian Family reunification immigration policies - Should the Parents and Grandparents (PGP) sponsorship intake program be based on a lottery or a first-come, first-served system? Or can a more effective hybrid system be put in place for sponsoring parents or grandparents of permanent residents or Canadians? What other factors can be considered to determine the selection of potential sponsors? - Sholola, Oluwafunmito (Université d'Ottawa | University of Ottawa, 2022)
As of 2016, 60.3% of new immigrants to Canada were admitted under the economic stream, 26.8% accounted for the family reunification class, while 11.6% were refugees (Statistics Canada 2017). Family migration is important to people, and residents and citizens of countries are always looking for ways to reunite with their loved ones. Over the years, there have been numerous changes made to the Canadian family reunification policies. This paper focuses on the Canadian Parent and Grandparent sponsorship program (PGP) and analyzes the problematic ways in which it has been administered and construed over the years. Using data from the Longitudinal Immigration Database (IMDB), Longitudinal Survey of Immigrants (LSIC), Labour Force Survey (LFS), Statistics Canada, Immigration, Refugee and Citizenship Canada (IRCC), and Canadian Census databases, the socio-demographic and economic profiles and outcomes of the family class migrants, specifically parents and grandparents, are compared to other migrant categories after landing. Based on public discourse, the family class migrants, especially parents and grandparents, have been portrayed as an economic burden to the Canadian welfare system, this misconception will be debunked throughout this paper. The current Parent and Grandparent sponsorship program administered is problematic as it solely adopts a lottery system without factoring other important criteria such as the sponsor’s length of stay and permanent residence in Canada, number of attempts to sponsor, maximum number of people applying for one source country and others. Although the current lottery program was introduced in an attempt to be fair to all potential sponsors, it has instead had the opposite effect because it is solely based on luck. The paper proposes recommendations including a hybrid program that will help address some of the perceived shortcomings of the current parents and grandparents sponsorship program, as family migration is an important fabric of Canadian society.